Total Quality Management in The Formation of Students Morals - Junaidi, Junaidi (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article reveals the uniqueness of Islamic Senior High School Insan Cedekia Jambi in shaping the morals of its students in the context of total quality management (TQM). How does this school implement TQM in forming the morals of its students? The findings of this research indicate that the implementation of TQM in forming the morals of MAN Insan Scholar Muaro Jambi students is carried out by reviewing the vision and mission and establishing madrasa programs for moral formation. Apart from that, schools also establish quality assurance and quality standards and create school culture by means of; positive habits, role models, spontaneous activities. All of this is also supported by a participative leadership style which is directed at increasing the motivation of teaching staff and maintaining relationships with customers, both in the educational, social, spiritual and public relations fields. Artikel ini mengungkap suatu keunikan pada Madrasah Aliyah Negerei Insan Cedekia Jambi dalam membentuk akhlak peserta didiknya dalam konteks total quality management (TQM). Bagaimana sekolah ini menerapkan TQM dalam pembentukan moral siswanya? Temuan penelitian ini menunjukkan bahwa penerapan TQM dalam pembentukan akhlak siswa MAN Insan Cendekia Muaro Jambi dilakukan dengan cara melakukan review visi dan misi serta menetapkan program madrasah dalam pembentukan akhlak. Di samping itu, sekolah juga menetapkan jaminan mutu dan standar mutu dan menciptakan kultur atau budaya sekolah dengan cara; pembiasaan positif, keteladanan, kegiatan spontan. Semua itu juga didukung dengan gaya kepemimpinan partisipatif yang diarahkan untuk peningkatan motivasi tenaga pendidik serta mempertahankan hubungan dengan pelanggan, baik dalam bidang pendidikan, sosial, kerohanian, dan kehumasan.